Bordered Pit Structure and Vessel Wall Surface Properties. Implications for Embolism Repair - Zwieniecki, Maciej Andrzej (American Society of Plant Physiologists, 2000)
The idea that embolized xylem vessels can be refilled while adjacent vessels remain under tension is difficult to accept if the cavitated vessels remain hydraulically connected to vessels under tension. A mechanism by which embolized conduits could be hydraulically isolated from adjacent conduits requires the existence of a non-zero contact angle and a flared opening into the bordered pit chamber such that a convex air-water interface forms at the entrance into the pit chamber. We measured the contact angle and pit chamber geometry for six species. The contact angle measured in the vessel lumen ranged between 42° to 55°, whereas the opening into the pit chamber ranged between 144° and 157°. If the surface properties within the pit chamber are similar to those in the lumen, a convex meniscus will form at the flared opening into the pit chamber. The maximum pressure difference between water in the lumen and gas in the pit chamber that could be stabilized by this interface was calculated to be within the range of 0.07 to 0.30 MPa.